2020
DOI: 10.30525/2256-0742/2020-6-2-81-92
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual Basis of Tax Policy Formation in the Globalization Conditions

Abstract: The purpose of the article is to analyze the tax systems of the countries of the European Union and Ukraine, the impact of individual indicators of the tax system on the economies development, study the possibility of applying the accumulated experience. The subject-matter of the study is the methodological and conceptual foundations of the tax policy-making process of the EU and Ukraine. Methodology. Based on the analyzed scientific literature on tax policy formulation of countries, the methodological princip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Although a large enterprise may not care too much about its cash flow, many small businesses choose to report on a regular basis on a quarterly or even monthly basis. By doing so, 345 they will be able to predict with much greater accuracy how healthy their cash flow will be in the future [378].…”
Section: Sale Of Invoices [373]mentioning
confidence: 99%
“…Although a large enterprise may not care too much about its cash flow, many small businesses choose to report on a regular basis on a quarterly or even monthly basis. By doing so, 345 they will be able to predict with much greater accuracy how healthy their cash flow will be in the future [378].…”
Section: Sale Of Invoices [373]mentioning
confidence: 99%
“…Academics have extensively delved into the investigation of elements that shape the Gini coefficient. Certain inquiries have centered around the effects of macroeconomic indicators on the Gini coefficient, encompassing aspects like economic advancement [1], distribution of wealth [2], and policy formulation [3]. Conversely, additional research has scrutinized micro-level determinants, for instance, education [4], health statuses [5], and the impacts of family arrangements [4] on the Gini coefficient.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from considering economic expansion and governmental strategies, contemporary investigations have directed their attention towards alternative variables that might affect the Gini coefficient. To illustrate, the work of Bourguignon and Morrison in 2002 unveiled that both globalization and technological advancement wield substantial influence over income inequality [3]. Furthermore, certain inquiries have delved into the impact of social and cultural components on the Gini coefficient.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Khalatur (2017) considers the state of agriculture in Ukraine and argues that the main reserves of agricultural development in Ukraine are government regulation, assessment of the attractiveness of the investment climate, the use of modern mechanisms of economic stimulation of production. Khalatur, Trokhymets & Karamushka (2020) analyzed the tax systems of the European Union and Ukraine, the impact of certain indicators of the tax system on economic development. The study of Khalatur, Khaminich, Dubovych, Budko & Karamushka (2020) showed that a multilevel system of investment decision-making is necessary to identify and form a positive synergy effect from the combination and interaction of assets and funding sources.…”
Section: Introductionmentioning
confidence: 99%